Blockchain to the Rescue: Improving Taxpayer Engagement with Blockchain - Allen, Christina; Potdar, Vidy (Thomson Reuters, 2022)
Although tax authorities are increasingly moving to digitalisation, there has been limited use of blockchain for assisting tax administration and compliance. This article discusses the potential use of blockchain technology for this purpose. In particular, the Australian tax system is considered in light of the challenges identified in the recent official report published by the House of Representatives Standing Committee on Tax and Revenue. These challenges result from the rising gig economy, complex work-related deduction rules for individual taxpayers and, more generally, tax evasion in the cash economy. To overcome these challenges, this article proposes a blockchain solution that increases taxpayer engagement with the tax and superannuation system. Not only would this solution benefit the Australian Government's ability to raise revenue and induce a good compliance culture, but a similar solution could be adopted in other jurisdictions.